On a generalized problem of bin packing - Trong, Nguyen (Journal of Computer Science and Cybernetics, 2015)
A generalization of the bin packing problem, called the DTMR problem is studied. The NP-completeness of DTMR is proved. Three heuristic algorithms-the CNN, the CHT and the CSX are described and the worst-case analysis of them are given. Some applications of the DTMR are shown.